Comparative Analysis of the Essential Oil of the Underground Organs of Valeriana spp. from Different Countries - Raal, A.; Kokitko, V. I.; Odyntsova, V. M.; Orav, A.; Koshovyi, O.; Кокітко, Валерія Ігорівна; Одинцова, Віра Миколаївна (My University, 2024)
Valeriana officinalis L. is a plant from the Caprifoliaceae family, which is widely distributed in various parts of the world, especially in Europe and Asia. All species of Valeriana are distinguished by their ability to synthesize essential oil, which has a powerful effect on the physiological and mental aspects of the human body. The aim was to study the qualitative and quantitative composition of essential oil from valerian roots, collected in different countries, using the gas chromatography method, and to establish marker compounds for valerian species. 13 samples of commercial roots with rhizomes of V. officinalis from nine countries of the world and a sample of Valeriana pratensis and Valeriana stolonifera growing in Ukraine were selected for the study. The essential oil was obtained from dried valerian roots by the distillation method described in the European Pharmacopoeia. To determine the component composition of the essential oils of the selected samples, the methods of gas chromatography with a mass spectrometric detector and capillary gas chromatography were used. The commercial samples of V. officinalis from different countries yielded 0.21%–1.03% of essential oil. Only six of 13 samples contained essential oil in an amount that satisfies the requirement of the European Pharmacopoeia standard (not less than 4 mL/kg). 150 compounds were identified in the essential oils of 13 samples of V. officinalis essential oils. The range and average content and coefficients of variation of the identified compounds were determined. The principal compounds of V. officinalis essential oils were bornyl acetate (1.6%–27.1%), valeranone (0.5%–17.9%), valerenal (0%–14.7%), camphene (0%–14.6%), α-fenchene (0%–10.6%), and valerenic acid (0%–8.5%). The samples of V. pratensis and V. stolonifera yielded rather high levels of essential oil (1.18% and 0.93%, respectively). Three chemotypes of V. officinalis samples were determined-bornyl acetate/valerenal, valeranone, and isovaleric acid. The composition of the three essential oils compared was rather similar. Based on the study results, we propose the following marker compounds for V. officinalis consistently present in all 16 examined samples: bornyl acetate (1.6%–27.1%), limonene (0.2–2.3), and valeranone (0.5%–17.9%). The study of samples from Ukraine indicates the prospects of using these species of the genus Valeriana with the aim of expanding the raw material base and creating potential herbal preparations with a sedative effect, which are extremely necessary for the population of the country in the war and post-war periods.
Keywords: Valeriana officinalis; Valeriana pratensis; Valeriana stolonifera; volatile compounds; terpenoids; chemotype